PENENTUAN INTERVAL PERGANTIAN KOMPONEN MESIN BUBUT MENGGUNAKAN METODE AGE REPLACMENT - Fakhrudin Ma’ruf; Said Salim Dahda (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2021)
Competition between industries currently requires the industry to continue to improve in improving the industrial system. Machine flexibility is one of the programs to improve industry's ability to increase competitiveness. In meeting consumer demand, general purpose machines have become one of the foundations for industrial systems in producing various types of products. Machine performance will decrease in line with the age of the machine / component and the length of the machine's operation. Maintenance planning / component replacement is one way to reduce downtime. A lathe is a general purpose machine, which has components that are often damaged, such as gear and control cables, which cause a lot to stop using the machine. Scheduling replacing components is a vital process in reducing lost time and minimizing costs arising from decreased machine performance. The focus of this research is determining the component replacement schedule that can meet these two criteria. This can be achieved by applying the age replacement method. The Age Replacement method is basically looking for a balance point between the probability of component failure and component reliability to obtain the optimal probability value of total down time. By estimating the pattern of component failure with the Weibull distribution, calculations are made for the two components that are most frequently damaged on a lathe. The results obtained are the time to replace the components, the replacement period and the costs arising from the optimal replacement of these components. By paying attention to the total down time probability value, it can be concluded that the optimal time to apply preventive replacement on the gear component and the control cable component.